Testing for bias and manipulation in the National Basketball Association playoffs - Zimmer, T.; Kuethe, T. H. (Journal of Quantitative Analysis in Sports, 2009)
The following paper examines potential sources of bias in National Basketball Association (NBA) playoffs. Employing NBA playoff data from 2003 through 2008, we investigate the expected margin of victory by the favored team. This method, by incorporating potentially mitigating variables, can also be used to test for potential bias and manipulation in tournament results.